2019
DOI: 10.18632/aging.102373
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic profiling of prognosis-related genes in the breast cancer immune microenvironment

Abstract: In the microenvironment of breast cancer, immune cell infiltration is associated with an improved prognosis. To identify immune-related prognostic markers and therapeutic targets, we determined the lymphocyte-specific kinase (LCK) metagene scores of samples from breast cancer patients in The Cancer Genome Atlas. The LCK metagene score correlated highly with other immune-related scores, as well as with the clinical stage, prognosis and tumor suppressor gene mutation status (BRCA2, TP53, PTEN) of patients in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“… Ito et al (2018) reported that the mRNA levels of the IRGs PD-L1 and CD8 may reflect the antitumor immune response, with low PD-1 and high PD-L1 mRNA levels independently implicated as poor prognostic markers in gastric cancer patients who underwent surgery. Bai et al (2019) reported the involvement of seven IRGs in the occurrence, development, malignant transformation, and pathology of breast cancer. Therefore, immune-related prognostic biomarkers are highly correlated with cancer progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… Ito et al (2018) reported that the mRNA levels of the IRGs PD-L1 and CD8 may reflect the antitumor immune response, with low PD-1 and high PD-L1 mRNA levels independently implicated as poor prognostic markers in gastric cancer patients who underwent surgery. Bai et al (2019) reported the involvement of seven IRGs in the occurrence, development, malignant transformation, and pathology of breast cancer. Therefore, immune-related prognostic biomarkers are highly correlated with cancer progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…ESTIMATE analysis can infer tumor cellularity and various TME cell infiltration via evaluating based on distinct properties of the gene transcriptional expression profiles of cancer samples. This bioinformatics algorithm has been widely used in tumor immune research, including in glioblastoma, hepatocellular carcinoma, acute myeloid leukemia and breast cancer [ 21 , 22 , 25 , 26 ]. In our study, we included 365 tumor samples and 19 adjacent normal tissue with completed clinical information from TCGA database .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of studies exploring the prognostic immune-genes for BC patients were reported. Bai et al ( 14 ) identified DEGs in BC samples with high and low lymphocyte-specific kinase (LCK) metagene scores. They obtained 115 genes, and found that 22 of them were independent predictors of OS in BC patients.…”
Section: Discussionmentioning
confidence: 99%